2010
DOI: 10.1002/adfm.201000383
|View full text |Cite
|
Sign up to set email alerts
|

High Tg Cyclic Olefin Copolymer Gate Dielectrics for N,N′‐Ditridecyl Perylene Diimide Based Field‐Effect Transistors: Improving Performance and Stability with Thermal Treatment

Abstract: A novel application of ethylene‐norbornene cyclic olefin copolymers (COC) as gate dielectric layers in organic field‐effect transistors (OFETs) that require thermal annealing as a strategy for improving the OFET performance and stability is reported. The thermally‐treated N,N′‐ditridecyl perylene diimide (PTCDI‐C13)‐based n‐type FETs using a COC/SiO2 gate dielectric show remarkably enhanced atmospheric performance and stability. The COC gate dielectric layer displays a hydrophobic surface (water contact angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 40 publications
9
50
0
Order By: Relevance
“…5a illustrates the AFM images and height profiles of pentacene and PTCDI-C13 thin films grown on COC and ZrO x dielectric layers, respectively. Surface morphologies of both the pentacene and PTCDI-C13 are in good agreement with previous reports where those organic semiconductors were grown on COC surfaces [29,40]. Pentacene thin films deposited on the COC surface exhibited large grains with sizes !1 mm and PTCDI-C13 molecules formed large and flat grains on a COC surface after thermal annealing at 120 C. The cross-sectional height profile of the PTCDI-C13 thin films revealed that the height of each layer was about 26.2 Å, corresponding to the d-spacing of the PTCDI-C13 molecules along the out-of-plane direction, as will be further discussed.…”
Section: Tablesupporting
confidence: 87%
See 3 more Smart Citations
“…5a illustrates the AFM images and height profiles of pentacene and PTCDI-C13 thin films grown on COC and ZrO x dielectric layers, respectively. Surface morphologies of both the pentacene and PTCDI-C13 are in good agreement with previous reports where those organic semiconductors were grown on COC surfaces [29,40]. Pentacene thin films deposited on the COC surface exhibited large grains with sizes !1 mm and PTCDI-C13 molecules formed large and flat grains on a COC surface after thermal annealing at 120 C. The cross-sectional height profile of the PTCDI-C13 thin films revealed that the height of each layer was about 26.2 Å, corresponding to the d-spacing of the PTCDI-C13 molecules along the out-of-plane direction, as will be further discussed.…”
Section: Tablesupporting
confidence: 87%
“…Thermally annealed PTCDI-C13 thin films grown on a COC/ZrO x dielectric surface exhibited [00l] out-of-plane reflections that correspond to a d- spacing of 26.4 Å, which agrees well with the results from AFM analysis. In addition, the PTCDI-C13 thin films exhibited many strong reflections along the q z axis at given q xy positions, which means that PTCDI-C13 crystals formed three-dimensional multilayered structures [29,40,43]. All of these results strongly suggest that both the pentacene and PTCDI-C13 molecules were grown on COC/ZrO x dielectric surfaces with favorable crystalline structures for efficient charge transport in OFETs, similar to previous reports of hydrophobic SAM or polymeric surfaces [26,29,40,42e44].…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…From the view of molecular design, PTCDI-C 13 H 27 is one of perylene derivatives that is favorable for the good stability in n -type organic transistors 20,26 . At the same time, PMMA is used as the dielectric of the transistor because its hydrophobic nature has been extensively shown to be favorable for good device stability 27,28 .…”
Section: Introductionmentioning
confidence: 99%